Cu2O-GO/SnO2 quantum dots for selective ethylene sensing at ppm to sub-ppm levels - Leangtanom, Pimpan; Wisitsoraat, Anurat; Chanlek, Narong; Lawan, Narin; Muangpil, Sairoong; Phanichphant, Sukon; Kruefu, Viruntachar (Sensors and actuators. B, Chemical, 2025)
In this work, hydrothermally synthesized SnO2 quantum dots (QDs), composited with graphene oxide (GO) and impregnated with 0–0.75 wt% cuprous oxide (Cu2O), were systematically studied for C2H4 sensing. Microscopic examination demonstrated multilayer GO dispersed quite uniformly within 3.0–3.7 nm quantum dots and X-ray spectroscopic evaluation indicated the presence of Cu2O structures. The gas-sensing measurement results revealed that GO and Cu2O materials provided synergistic enhancements of C2H4 response and selectivity. The Cu2O-GO/SnO2 nanocomposite exhibited a decent response of 24.8 with a short response time of 36 s to 50 ppm C2H4 and a low C2H4 detection limit of 9 ppb at a moderately low operational temperature of 250°C. Additionally, it displayed high C2H4 selectivity against H2S, NO2, NH3, CH4, CO, CO2, C2H5OH, C6H12O and C6H5CH3. Moreover, it offered good response repeatability, low humidity dependency, and decent medium-term stability. Therefore, Cu2O-GO/SnO2 QDs could be a potential candidate for advanced C2H4-sensing applications. [Display omitted] •Hydrothermally prepared SnO2 quantum dots were loaded with graphene oxide and Cu2O.•Multilayer graphene oxide sheets dispersed on 3–3.7 nm SnO2 quantum dots were observed.•Response to 50 C2H4 at 250°C raised from 5.6 to 24.8 with GO and 0.5 wt% Cu loadings.•Cu2O-GO/SnO2 sensor with 0.5 wt% Cu offered a low C2H4 detection limit of 9 ppb.•The sensor exhibited high C2H4 selectivity against H2S, NO2, NH3, CH4, CO, CO2, C2H5OH, C6H12O and C6H5CH3.